SABAR DAN SHOLAT SEBAGAI PENOLONG DALAM AL – QUR’AN SURAH AL – BAQARAH AYAT 153 - Rini Antika Sari Rangkuti; Sriwahyuni Pasaribu (Pusat Riset dan Inovasi Nasional, 2023)
The Qur'an not only regulates the relationship between humans and their Lord, but also regulates the relationship between humans and humans for the sake of happiness in life in this world and in the hereafter. Allah SWT explains the meaning of patience and guidance to ask for help through patience and prayer contained in the Al-Qur'an Al-Baqarah verse 153. The research method used in this research is qualitative with content analysis. Prayer is a means of presenting a solution, and this is the best way, no matter how hard the problem is, return to Allah, pray, prostrate, bow down, bow before Allah, humiliate yourself, and let Allah guide our solution. Whatever we do will not change God's destiny without His permission, so prayer is the bright way to the solution to the magnitude of our problems. With prayer we will find peace and that is where the solution will be present, Allah will sincerely cooperate with us to solve our problems.